The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12880-015-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated lesion detection on MRI scans using combined unsupervised and supervised methods

Abstract: BackgroundAccurate and precise detection of brain lesions on MR images (MRI) is paramount for accurately relating lesion location to impaired behavior. In this paper, we present a novel method to automatically detect brain lesions from a T1-weighted 3D MRI. The proposed method combines the advantages of both unsupervised and supervised methods.MethodsFirst, unsupervised methods perform a unified segmentation normalization to warp images from the native space into a standard space and to generate probability ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Moreover, the lesions present a high degree of discontinuity which was a big challenge to this algorithm, thereby resulting in a very poor performance as can be seen in Table 1 where INNN17 has a 0.732 overlap and INNN21 has a 0.511 performance. We also compared the proposed method against the Automated Lesion Detection on MRI Scans Using Combined Unsupervised and Supervised Methods by Guo et al [34] and Multiplicative Intrinsic Component Optimization (MICO) [35] method by Li et al, and their results are reported in Figures 11, 12, and 13.…”
Section: Evaluation and Experimental Resultsmentioning
confidence: 99%
“…Moreover, the lesions present a high degree of discontinuity which was a big challenge to this algorithm, thereby resulting in a very poor performance as can be seen in Table 1 where INNN17 has a 0.732 overlap and INNN21 has a 0.511 performance. We also compared the proposed method against the Automated Lesion Detection on MRI Scans Using Combined Unsupervised and Supervised Methods by Guo et al [34] and Multiplicative Intrinsic Component Optimization (MICO) [35] method by Li et al, and their results are reported in Figures 11, 12, and 13.…”
Section: Evaluation and Experimental Resultsmentioning
confidence: 99%
“…43 The combined unsupervised and supervised components along with SVM classi¯er achieved an average Dice coe±cient of 73.1% for detecting stroke lesion in T1-weighted MRIs. 44 An automated approach based on unsupervised classi¯cation with fuzzy c-means clustering with the self-adjusted intensity thresholds detected cerebral infarct lesions with a DSI of 89.9%. 45 An automated approach based on Bayesian MRF was successfully used to segment stroke lesion in FLAIR MRI images with a Dice similarity coe±cient of 0.60.…”
Section: Discussionmentioning
confidence: 99%
“…The SVM is considered as one of the supervised learning models used in various applications such as segmentation, object recognition, speaker identification, and medical diagnosis (10,38). It was used to classify voxels into normal and pathological tissue (45)(46)(47).…”
Section: Machine-learning-based Segmentationmentioning
confidence: 99%